KEPASTIAN HUKUM TERHADAP PEMBERIAN RUMAH HIBAH DALAM PERSPEKTIF FIQH MUAMALAH : Studi Kasus Didesa Deah Pangwa Kecamatan Tringgadeng Kabupaten Pidie Jaya - Ilyas Khairani, Wilda; Matsyah, Ajidar; bin Adnan , Boihaqi (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2026)
A grant (hibah) is a legal act carried out voluntarily by a person to transfer ownership of property to another party without compensation while the grantor is still alive. In practice, grants made without written evidence and without complying with legal requirements often lead to disputes, particularly within families. This study aims to analyze the legal certainty of house grants made without written proof from the perspective of fiqh muamalah and to examine dispute resolution efforts concerning the control or retrieval of granted houses. This research employs a normative-sociological approach with a qualitative descriptive method. The data were obtained through field research conducted in Deah Pangwa Village, Tringgadeng District, Pidie Jaya Regency, supported by library research consisting of statutory regulations, fiqh muamalah literature, and relevant academic works. The findings indicate that house grants made without written evidence create legal uncertainty and have the potential to trigger conflicts among heirs. From the perspective of fiqh muamalah, a valid grant must fulfill its pillars and conditions, including the clarity of the object, the consent of the parties, and actual possession by the grantee. Dispute resolution efforts may be pursued through family deliberation, customary mediation, or legal proceedings by prioritizing the principles of justice and public benefit (maslahah). This study is expected to provide guidance to the community regarding the importance of legal procedures in granting practices to ensure legal certainty and prevent future disputes.